2020
DOI: 10.1128/jb.00157-20
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan Sensing Prevents Quiescence and Promotes Quorum-Independent Colony Growth of Uropathogenic Escherichia coli

Abstract: Uropathogenic Escherichia coli (UPEC) are the leading cause of human urinary tract infections (UTIs) and many patients experience recurrent infection after successful antibiotic treatment. The source of recurrent infections may be persistent bacterial reservoirs in vivo that are in a quiescent state and thus are not susceptible to antibiotics. Here, we show that multiple UPEC strains require a quorum to proliferate in vitro with glucose as the carbon source. At low cell density, the bacteria remain viable but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Beyond GlcNAc, other PGN-derived fragments have been reported to display a clear capacity for bacterial behavior modulation. This would be the case of the stem tetra- and penta-peptides (P4 and P5) cleaved from the glycan chains of PGN, which have been recently demonstrated to prevent the quiescent nonproliferative status that appears at low population density in uropathogenic E. coli (DiBiasio et al 2020 ). Interestingly, this metabolic response is obtained when providing these fragments exogenously, both obtained from E. coli and from Gram-positive PGN, indicating that the nature of the third amino acid in the chain (DAP vs. l -lysine, respectively) is not important to activate this quorum sensing-independent growth.…”
Section: The Exogenous Source Of Pgn Fragments: Not Only Intra- But A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond GlcNAc, other PGN-derived fragments have been reported to display a clear capacity for bacterial behavior modulation. This would be the case of the stem tetra- and penta-peptides (P4 and P5) cleaved from the glycan chains of PGN, which have been recently demonstrated to prevent the quiescent nonproliferative status that appears at low population density in uropathogenic E. coli (DiBiasio et al 2020 ). Interestingly, this metabolic response is obtained when providing these fragments exogenously, both obtained from E. coli and from Gram-positive PGN, indicating that the nature of the third amino acid in the chain (DAP vs. l -lysine, respectively) is not important to activate this quorum sensing-independent growth.…”
Section: The Exogenous Source Of Pgn Fragments: Not Only Intra- But A...mentioning
confidence: 99%
“…Meanwhile, the known mechanism for the uptake of these peptides into the cytosol, namely the oligo-peptide permease system Opp, seems dispensable for the response, from which it is deduced that there exists either an additional unknown transporter for the aforementioned P4 and P5, or a sensor responsible for their detection in the periplasm. Moreover, shorter stem peptides or larger PGN fragments including sugar moieties did not exert the abovementioned effects on the bacterium, suggesting quite a tight array of PGN fragments to which the unidentified sensor/regulator could respond (DiBiasio et al 2020 ). Identification of this sensor/regulator as well as the downstream signaling events causing the prevention of quiescence is a very interesting topic worth delving into, because of the clear bacterial fitness-related implications.…”
Section: The Exogenous Source Of Pgn Fragments: Not Only Intra- But A...mentioning
confidence: 99%
“…We introduced a mini-Tn5 transposon in the UPEC genome (CFT073) by conjugative transfer from a donor strain (ATM161), and then screened a culture of recipients (10 4 CFU ml -1 ) for growth on glucose minimal agar supplemented with kanamycin. We previously reported that UPEC cells (CFT073) become quiescent on glucose minimal agar at low plating density (<10 6 CFU ml -1 ) but proliferate rapidly at high plating density (>10 6 CFU ml -1 ) (28,29). We isolated 21 mutant strains that formed colonies on glucose minimal agar when plated at low cells density (10 4 CFU ml -1 ) and identified the mini-Tn5 insertion site by arbitrarily-primed PCR and sequencing (34).…”
Section: Mini-transposon Screen Reveals Regulators Of Quiescencementioning
confidence: 99%
“…Next, we tested if known proliferants could prevent quiescence and promote proliferation of CFT073 ∆ihfB::kan (JM028) and CFT073 ∆zapE::kan (JM023) strains complemented with expression plasmids. Proliferant cues that were previously identified include peptidoglycan (PG) tetra-and pentapeptides and the amino acids L-lysine (1 mM) and L-methionine (1 mM) (28,29).…”
Section: Mini-transposon Screen Reveals Regulators Of Quiescencementioning
confidence: 99%
See 1 more Smart Citation